Perfectly Norman - Percival, Tom, 1977- (Percival, Tom, 1977- Big bright feelings., 2018)
Norman is thrilled to discover he grew a pair of wings overnight, but his excitement turns to doubt when he realizes he is now different from everyone else, causing him to question whether there is such thing as perfectly normal.